Sclerotium rolfsii에 의한 할미꽃 흰비단병 - 권진혁(Jin Hyeuk Kwon); 황갑춘(Gap Chun Hwang); 이슬비(Seol Bi Lee); 최용조(Yong Jo Choi); 이상대(Sang Dae Lee); 응웬레민(Le Minh Nguyen) (Sigmulbyeong yeon'gu, 2015)
Sclerotium rot on Pulsatilla koreana was observed in the exhibition field of Jinju Agriculture Technology Center in July 2013. The infected plants showed water-soaked, blighted and rotted symptoms. White mycelial mats spread over lesions, and then numerous sclerotia were formed on flower stalk and flower stem near the soil line. The sclerotia were globoid in shape, 1-3 mm in size and white to brown in color. The optimum temperature for mycelial growth and sclerotia formation on PDA was $30^{°}C$ and the hyphal width was $4-8μm$. The typical clamp connections were observed in the hyphae of the fungus grown on PDA. For molecular identification, the complete ITS rDNA sequence of the causal fungus was sequenced and analyzed. On the basis of mycological characteristics, ITS rDNA sequence analysis, and pathogenicity to host plants, this fungus was identified as Sclerotium rolfsii Saccardo. This is the first report of sclerotium rot on Pulsatilla koreana caused by S. rolfsii in Korea. 2013년 7월 경상남도 진주시농업기술센터 양묘장 전시포에 재배중인 할미꽃에서 흰비단병 증상이 발생하였다. 병징은 할미꽃의 꽃줄기와 꽃자루 부분이 수침상으로 물러지면서 부패되어지고 서서히 시들면서 포기 전체가 말라 죽었다. 병반부와 토양 표면에 흰색의 곰팡이가 발생하며 갈색의 작은 둥근 균핵이 많이 형성되었다. 감자한천배지에서 균총은 흰색이고 배양 기간이 경과됨에 따라 갈색의 작은 둥근 균핵을 많이 형성하였다. 균핵의 크기는 1-3 mm이며 균사의 폭은 $4-9μm$였다. 균사생육과 균핵 형성 적온은 $30^{°}C$이었다. 균사특유의 clamp connection이 관찰되었다. 할미꽃에서 발생한 병징과 병원균의 균학적 특징, 그리고 ITS rDNA 염기서열 비교분석 결과, 이 병을 S. rolfsii Saccardo에 의한 할미꽃 흰비단병으로 명명하고자 제안한다.